2017
DOI: 10.7324/japs.2017.71025
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Carob Pods Extract (Ceratonia siliqua L.) against Cyclophosphamide Induced Alterations in Bone Marrow and Spleen of Rats

Abstract: Cyclophosphamide (CYP) belongs to the anticancer drugs that exhibit potentially life-threatening effects on the immune and hematopoietic systems. The study aimed to assess efficiency of carob pods extract against the adverse CYP effect on spleen and lymphatic tissues which are the most sensitive components of immune system. In the present study, the hematological indices and markers of oxidative stress were assessed. In addition, the native protein, lipoprotein patterns, calcium moiety of native protein, catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Our results are in accordance with other studies that showed a reduction in lymphoid cellularity of the spleen in CTX-treated rats (Senin et al, 2020). Moreover, the greatest cyclophosphamide cytotoxicity against cells of the immune and hematopoietic systems was due to the active and continuous replication of their DNA resulting in serious cytotoxic damage (Abd Elhalim et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in accordance with other studies that showed a reduction in lymphoid cellularity of the spleen in CTX-treated rats (Senin et al, 2020). Moreover, the greatest cyclophosphamide cytotoxicity against cells of the immune and hematopoietic systems was due to the active and continuous replication of their DNA resulting in serious cytotoxic damage (Abd Elhalim et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Concerning the current work, using CD20, a marker of the B lymphocyte population, it revealed a weak reaction in the spleen of animals treated with CTX due to the severe damage of B lymphocytes in the white pulp. This can be attributed to the profound depletion of B cells because of dose-intensive cytotoxic antineoplastic therapy (Abd Elhalim et al, 2017). Moreover, Al-Joufi et al ( 2022) findings suggested that CTX suppresses the lymphocyte count and function in the spleen and Peyer's patches of the ileum in a timedependent fashion, especially B cells which could lead eventually to bacteraemia.…”
Section: Discussionmentioning
confidence: 99%